2008
DOI: 10.1111/j.1600-051x.2008.01217.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after treatment of intra‐bony defects with an EMD/synthetic bone graft or EMD alone: a multicentre randomized‐controlled clinical trial

Abstract: The results of the present study showed similar clinical outcomes following both treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
111
7
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(132 citation statements)
references
References 41 publications
12
111
7
2
Order By: Relevance
“…EMD may influence softtissue healing, which may cause better postoperative patient perceptions, in addition to its capability of promoting periodontal regeneration 1,12,18,24) . Lack of pain, improved healing of the soft tissues and limited inflammation of the operated areas have been common clinical observations following EMD therapy 8,9) . Ozcelik et al 14) reported that patient perceptions on the immediate post-operative period were significantly better in the non-surgery and surgery with EMD groups when compared with the surgery group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMD may influence softtissue healing, which may cause better postoperative patient perceptions, in addition to its capability of promoting periodontal regeneration 1,12,18,24) . Lack of pain, improved healing of the soft tissues and limited inflammation of the operated areas have been common clinical observations following EMD therapy 8,9) . Ozcelik et al 14) reported that patient perceptions on the immediate post-operative period were significantly better in the non-surgery and surgery with EMD groups when compared with the surgery group.…”
Section: Discussionmentioning
confidence: 99%
“…While it is imperative to evaluate the efficacy of a treatment modality in longitudinal studies, it is equally important to understand the healing process during early periods. It is assumed that EMD has an effect on the critical steps of periodontal wound healing that occur during the early healing phase 9) . In our teaching hospital, surgical treatment with EMD has been the treatment of choice for patients requesting periodontal regenerative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Enamel matrix derivative is derived from porcine tooth buds and is currently available in a commercial formulation (Emdogain ® Gel, Biora AB, Malmö, Sweden) 3) . Since its introduction, extensive research regarding EMD has been carried out, and the results have demonstrated its ability to encourage periodontal regeneration 4,6,7,17,22) . There was, however, a substantial degree of variability in treatment outcome with a pronounced center effect 4,13) .…”
Section: Introductionmentioning
confidence: 99%
“…According to a study of Jepsen et al [19] it has been shown that the clinical outcomes after treatment of intra-bony defects with an EMD/synthetic bone graft or EMD alone could bring similar but good results considering the shape of the defects. In our case, a remarkable improvement of the GR, PD and CAL records were achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Gingival recession has been especially correlated with lip studs or labrets [1,4,15,16] and frequently occurs on the labial aspect of the lower central incisors [3,4,[16][17][18][19][20][21]. Gingival recession, particularly on the lingual aspect of the mandibular anterior teeth, has also been associated with tongue piercing [3,4,16,17].…”
Section: Introductionmentioning
confidence: 99%